T1ρ MRI detects cartilage damage in asymptomatic individuals with a cam deformity. Issue 6 (2nd December 2015) - Anwander, Helen; Melkus, Gerd; Rakhra, Kawan S.; Beaulé, Paul E.
ABSTRACT: Hips with a cam deformity are at risk for early cartilage degeneration, mainly in the anterolateral region of the joint. T1ρ MRI is a described technique for assessment of proteoglycan content in hyaline cartilage and subsequently early cartilage damage. In this study, 1.5 Tesla T1ρ MRI was performed on 20 asymptomatic hips with a cam deformity and compared to 16 healthy control hips. Cam deformity was defined as an alpha angle at 1:30 o'clock position over 60° and/or at 3:00 o'clock position over 50.5°. Hip cartilage was segmented and divided into four regions of interest (ROIs): anterolateral, anteromedial, posterolateral, and posteromedial quadrants. Mean T1ρ value of the entire weight bearing cartilage in hips with a cam deformity (34.0 ± 4.6 ms) was significantly higher compared to control hips (31.3 ± 3.2 ms, p  = 0.050). This difference reached significance in the anterolateral ( p  = 0.042) and posteromedial quadrants ( p  = 0.041). No significant correlation between the alpha angle and T1ρ values was detected. The results indicate cartilage damage occurs in hips with a cam deformity before symptoms occur. A significant difference in T1ρ values was found in the anterolateral quadrant, the area of direct engagement of the deformity, and in the posteromedial quadrant. To conclude, T1ρ MRI can detect early chondral damage in asymptomatic hips with a cam deformity. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:1004–1009, 2016.